Technological prototype with artificial intelligence for military security in river environments (2024)
Maritime and river security is one of the main concerns of military forces due to the large number of illicit activities that occur. Not to mention the extensive areas that must be monitored, and the weather conditions that can occur. Currently, technologies have become fundamental to leave aside manual surveillance for intelligent systems that allow remote sensing, traffic control, and object detection. Based on the aforementioned problems, the purpose of this research was to design a technological prototype with artificial vision based on an artificial intelligence model to detect water vessels and people in river environments as a support tool for military security. The prototype used at hardware level a Raspberry Pi 3 card and four pre-trained models based on R-CNN, YOLO, EfficientDet and SSD (single shot multibox). The best-performing model was the Mobilnet V2 SSD, with an mAP of 0.83 and an FPS of 5. Finally, this tool can contribute to strengthening the strategic, tactical, and operational capabilities of actors in the military intelligence sector, aimed at protecting sovereignty and territorial integrity to establish an environment of security in society.